2018
DOI: 10.1080/15376516.2018.1485804
|View full text |Cite
|
Sign up to set email alerts
|

Potentiating effect of acetaminophen and carbon tetrachloride-induced hepatotoxicity is mediated by activation of receptor interaction protein in mice

Abstract: When multiple drugs or chemicals are used in combination, it is important to understand the risk of their interactions and predict potential additive effects. The aim of the current study was to investigate the molecular mechanism(s) accounting for the additive/synergistic effect of combination treatment with acetaminophen (APAP) and carbon tetrachloride (CCl). Mice were intraperitoneally administered vehicle or 100 mg/kg (5 mL/kg) APAP and 30 min after vehicle or 15 mg/kg (5 mL/kg) CCl. Sixteen hours after tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…8) We previously reported that streptomycin, which shows nephrotoxicity, was highly toxic following dark-phase exposure and less toxic following light-phase exposure. 9) These findings of the previous studies do not contradict with those of the present study, suggesting that differences in the toxicity of BB and the three BB intermediate metabolites are attributed to their target organs. BB targets the liver, whereas its intermediate metabolites target the kidneys.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…8) We previously reported that streptomycin, which shows nephrotoxicity, was highly toxic following dark-phase exposure and less toxic following light-phase exposure. 9) These findings of the previous studies do not contradict with those of the present study, suggesting that differences in the toxicity of BB and the three BB intermediate metabolites are attributed to their target organs. BB targets the liver, whereas its intermediate metabolites target the kidneys.…”
Section: Resultssupporting
confidence: 65%
“…In this study, we targeted "chronotoxicology" as we have previously suggested the relationship between the administration timing and the toxicity severity of chemicals. [7][8][9] Our previous study demonstrated notable daily fluctuations in the severity of toxic responses to BB in mice, i.e., mice were more tolerant to BB-induced hepatic injury during the dark-phase exposure (2:00) than during the light-phase exposure (14:00). 8) Although BB showed mild nephrotoxicity, chronotoxicity was not observed in the kidneys.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress is one of landmark events of APAP-induced acute hepatic injury [32]. In experiments of rodent model, routine dose of APAP were mainly involved in glucuronidation and sulfation, and the nontoxic metabolites were then excreted through vile and urine [33,34]. However, when excessive APAP is oxidated to NAPQI by cytochrome P450 (CYP), which binds with GSH to inhibit toxic responses [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Protein samples (30 μg) were subjected to gradient sodium dodecyl sulfate-polyacrylamide gel electrophoresis (BioRad, Hercules, CA, USA) and transferred to a polyvinylidene difluoride membrane using Trans-Blot Turbo Transfer System (BioRad). Next, the membrane was incubated with mouse anti-α-smooth muscle actin (anti-αSMA) monoclonal antibody (Santa Cruz), mouse anti-β-actin monoclonal antibody (MBL, Aichi, Japan), rabbit anti-c-Jun N-terminal kinase (JNK) polyclonal antibody, rabbit anti-phospho-JNK monoclonal antibody, rabbit-anti extracellular signal-regulated kinase (ERK) 1/2 monoclonal antibody, rabbit anti-phospho-ERK1/2 monoclonal antibody, rabbit-anti p38 monoclonal antibody, rabbit anti-phospho-p38 monoclonal antibody, peroxidase-conjugated anti-rabbit IgG (Cell Signaling Technology, Beverly, MA, USA), and peroxidase-conjugated anti-mouse IgG (BioRad) using previously described conditions [ 29 ]. Immuno-reactive bands were visualized with an ECL system (BioRad).…”
Section: Methodsmentioning
confidence: 99%